Sarcopenia and dosimetric parameters in relation to treatment-related leukopenia and survival in anal cancer - Martin P. Nilsson; Anders Johnsson; Jonas Scherman (Radiation Oncology, 2021)
Abstract Background Treatment-related white blood cell (WBC) toxicity has been associated with an inferior prognosis in different malignancies, including anal cancer. The aim of the present study was to investigate predictors of WBC grade ≥ 3 (G3+) toxicity during chemoradiotherapy (CRT) of anal cancer. Methods Consecutive patients with locally advanced (T2 ≥ 4 cm—T4 or N+) anal cancer scheduled for two cycles of concomitant 5-fluorouracil and mitomycin C chemotherapy were selected from an institutional database (n = 106). All received intensity modulated radiotherapy (IMRT; mean dose primary tumor 59.5 Gy; mean dose elective lymph nodes 45.1 Gy). Clinical data were extracted from medical records. The highest-grade WBC toxicity was recorded according to CTCAE version 5.0. Pelvic bone marrow (PBM) was retrospectively contoured and dose-volume histograms were generated. The planning CT was used to measure sarcopenia. Dosimetric, anthropometric, and clinical variables were tested for associations with WBC G3+ toxicity using the Mann–Whitney test and logistic regression. Cox proportional hazard regression was used to assess predictors for overall survival (OS) and anal cancer specific survival (ACSS). Results WBC G3+ was seen in 50.9% of the patients, and 38.7% were sarcopenic. None of the dosimetric parameters showed an association with WBC G3+ toxicity. The most significant predictor of WBC G3+ toxicity was sarcopenia (adjusted OR 4.0; P = 0.002). Sarcopenia was also associated with an inferior OS (adjusted HR 3.9; P = 0.01), but not ACSS (P = 0.07). Sensitivity analysis did not suggest that the inferior prognosis for sarcopenic patients was a consequence of reduced doses of chemotherapy or a prolonged radiation treatment time. Patients who experienced WBC G3+ toxicity had an inferior OS and ACSS, even after adjustment for sarcopenia. Conclusions Sarcopenia was associated with increased risks of both WBC G3+ toxicity and death following CRT for locally advanced anal cancer. In this study, radiation dose to PBM was not associated with WBC G3+ toxicity. However, PBM was not used as an organ at risk for radiotherapy planning purposes and doses to PBM were high, which may have obscured any dose–response relationships.